A8.2 Oral administration of bovine milk-derived extracellular vesicles diminishes cartilage pathology in two arthritis models. (13th February 2015) - Arntz, OJ; Pieters, BCH; de Oliveira, MC; Bennink, MB; Plem, van Lent; van der Kraan, PM; Koenders, MI; van de Loo, FAJ
Abstract : Development of rheumatoid arthritis (RA) is associated with environmental factors and several studies show a connetion with diet. Recently, exosomes are identified in both bovine and human breast milk. Exosomes are small (30–200 nm) membrane-derived extracellular vesicles that carry immunoregulatory microRNAs, proteins and lipids, and mediate intercellular communication. In this study, we investigated the effect of oral intake of bovine milk-derived extracellular vesicles (BMEVs) on spontaneous polyarthritis in IL-1Ra deficient mice and on collagen-induced arthritis (CIA) in DBA1/J mice. BMEVs were isolated from skimmed milk by ultracentrifugation and characterised by nanoparticle tracking analysis, electron microscopy, anti-CD63 staining, and PCR. BMEVs were labelled with PKH-67 to determined the uptake by cells using FACS and confocal microscopy. TGFb levels were measured with a CAGA-fLuc reporter construct. Naïve T cells were cultured for 5 days with an inflammatory cocktail in the presence of milk exosomes, to induce Th17 differentiation as assessed by RORgT and IL-17 mRNA expression. In IL-1Ra -/- mice, BMEVs were administered daily by oral gavage starting at week 5 till 15 after birth and arthritis was scored macroscopically. In CIA, mice received BMEVs via their drinking water starting 1 week before immunisation till day 40. Arthritis was scored macroscopically and on histology. To determine the effect on immunity, serum IgG levels were measured by ELISA, T-cell specific gene expression (T-bet, RORgT, GATA-3) in LPS stimulated splenocytes by Luminex and RT-qPCR. The BMEV particle size was around 120 nm and expressed the exosome markers tetraspanin CD63, miRNA's (miR-let-7a, -16, -30a, -92a, -223), and milk specific beta-casein and beta-lactoglobulin mRNA. Acidification, up to gastric acid level (pH 2) left the BMEVs intact, and did not alter their inhibitory effect on NFkB-activation. Active TGFb was detected on BMEVs and incubation of naïve T cells with BMEVs induced significant Th17 differentiation to a similar extent as TGFb. However, BMEVs treatment of mice showed a delayed onset of arthritis in both the IL-1Ra -/- and CIA model. Diminished cartilage pathology and bone marrow inflammation was observed in both models. BMEVs also reduced the circulation levels of MCP1 and IL-6 levels and their production by splenic cells. In BMEV treated CIA, circulating anti-collagen type II IgGa level was reduced and this was accompanied by reduced splenic Th1 and Th17 numbers. Bovine milk-derived extracellular vesicles are bioactive, probably can withstand the harsh conditions of the gut, and oral delivery ameliorates disease in two RA models.